Effects of Sleeve Gastrectomy as a Bariatric Surgery on Weight of Dietary Induced Obese Rats. - Alrubaiea, Abdul -hadiL. (AL-Kindy College Medical Journal, 2014)
Background: Obesity is becoming the healthcare epidemic world wide.Obesity is associated with reduced life expectancy, increased morbidity and mortality, and greater healthcare costs.Bariatric surgery is the only effective treatment for morbid obesity and is gaining increasing popularity. There has been a steady rise in the numbers and types of bariatric operations done worldwide in recent years butnon of prove to be ideal .Animal studies and use of animal models are significant element in the evolution of medical knowledge and the use of animals as a model for bariatric surgery is of importance to study the mechanisms of these operationsa and also help to develop new technique in management of obesity.Objectives:Study of effects of sleeve gastrectomy as bariatric surgery procedures on weight of dietary induced obese rats (DIO).Methods:Eighteen adult rats with diet induced obesity (DIO) divided into two groups, the first (n=9) group exposed to sleeve gasterectomy (SG)under general anesthesia , the second(n=9) is the sham (control) group. Postoperative care of the animals done as required and the weight of the rats were measured weekly for 6 weeks .Results:. Follow up for 6 weeks post-operative . Four rats from SG group were died: two in the first day , second and 6th post operative day .Postmortem done with evidence of gastric leak in two of them. Two sham operated rats were died. The dead rats were cancelled from the study when body weight calculated. Average weight were 425gram and 420gram for SG and Sham respectively before surgery. Both groups experience some weight loss in the first week after surgery while the SG group start losing more weight , while the sham group are starting to maintain its normal weight until the end of the experiment.Conclusions:. Sleeve Gastrectomy as a bariatric procedure are successfully reduce the weight of DIO rats . Development of animal model for bariatric procedure is of great importance to test the effects of different bariatric procedures on the weight, and translate these procedures on human.